2007
DOI: 10.1007/s00424-007-0288-1
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear phospholipid signaling: phosphatidylinositol-specific phospholipase C and phosphoinositide 3-kinase

Abstract: Over the last 20 years, numerous studies have demonstrated the existence of nuclear phosphoinositide signaling distinct from the one at the plasma membrane. The activation of phosphatidylinositol-specific phospholipase C (PI-PLC) and phosphoinositide 3-kinase (PI3K), the generation of diacylglycerol (DAG) and the accumulation of the 3-phosphorylated phosphoinositides have been documented in the nuclei of different cell types.In this review, we summarize some recent studies of the subnuclear localization, mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 85 publications
0
22
0
Order By: Relevance
“…In S. cerevisiae, there is only one Plc1 encoded by the gene PLC1 (9,10). In mammalian cells, at least 13 Plc isoforms have been identified, and many of them, including Plc-␤, -␥, -␦, and -, have been found to be activated in nuclei of cells at a particular phase of the cell cycle (27). A sole Plc1 in yeasts corresponds best to the mammalian Plc-␦1, and this is the isoform that has been most consistently found to be associated with nuclei of mammalian cells somewhere at the beginning of S phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In S. cerevisiae, there is only one Plc1 encoded by the gene PLC1 (9,10). In mammalian cells, at least 13 Plc isoforms have been identified, and many of them, including Plc-␤, -␥, -␦, and -, have been found to be activated in nuclei of cells at a particular phase of the cell cycle (27). A sole Plc1 in yeasts corresponds best to the mammalian Plc-␦1, and this is the isoform that has been most consistently found to be associated with nuclei of mammalian cells somewhere at the beginning of S phase.…”
Section: Discussionmentioning
confidence: 99%
“…In synchronized NIH3T3 cells, the level of Plc-␦1 in nuclei increased at the G 1 /S boundary (7), and "knockdown" of Plc-␦1 in rat C6 glioma cells significantly decreased proliferation and delayed the progression through S phase (28). Enhanced degradation of cyclin E levels in mammalian cells (28) has been suggested to mediate the role of Plc in cell cycle control, but it is not clear how the enzyme might interact with the cell cycle machinery to regulate progression through different phases of the cell cycle (9,27).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ADP-ribosyl cyclase enzyme that is responsible for the production of cyclic ADP ribose (cADPR) and/or NAADP is localised in the nucleus (Adebanjo et al, 1999;Bezin et al, 2008a;Trubiani et al, 2008). In addition, it has been well established that nuclei possess phosphoinositide signalling mechanisms that are similar to, but distinct from, those that occur at the plasma membrane, and which can lead to InsP 3 production (Visnjic and Banfic, 2007;Ye and Ahn, 2008). and phosphoinositide-specific phospholipase C (PtdIns-PLC) (Downes et al, 2005).…”
Section: Autonomous Generation Of Ca 2+ -Mobilising Messengers In Thementioning
confidence: 99%
“…It is known that PtdIns-PLCβ isoforms are activated at the plasma membrane by G-proteincoupled receptors and are responsible for rapid InsP 3 production and acute Ca 2+ signals (see Box 2). In the nucleus, however, PtdIns-PLCβ 1 plays an important role in signalling events that are evoked by growth-factor-receptor stimulation (Visnjic and Banfic, 2007). For example, PtdIns-PLCβ 1 was found to be essential during the differentiation of skeletal muscle myoblasts .…”
Section: Autonomous Generation Of Ca 2+ -Mobilising Messengers In Thementioning
confidence: 99%
“…However, downstream targets of Plc-generated second messengers in nuclei have remained poorly described (reviewed in Visnjic and Banfic, 2007;Follo et al, 2014). Irvine et al (1993) first observed that there are many similarities between nuclear phospholipid signalling in mammals and phospholipid signalling in the budding yeasts Saccharomyces cerevisiae (Irvine, 2003).…”
Section: Introductionmentioning
confidence: 99%